Analisis Audit Energi Hotel Sintesa Peninsula Manado - Glori V. Jr. Agus; Meita Rumbayan; Vecky C. Poekoel (Universitas Sam Ratulangi, 2019)
Abstract — With increasing needs of electrical energy and the reliability of a system of electric power must also be directly proportional to the needs of electrical energy. Analysis Audit Energy is A technique that is used to calculate the amount of energy consumption in building and recognize ways to save it. Analysis Audit Energy of Manado Sintesa Peninsula Hotel, aims to determine the energy usage and energy utilization conditions as well as energy saving opportunities in the hotel Sintesa Peninsula Manado.From data obtained from several rooms, some have not met the criteria and there are also rooms that have met the criteria of the energy audit. from this analysis planning is used to optimize the use of electrical energy and other energy utilization in hotel Sintesa Peninsula Manado so that it can be more economical and can also be one of the references for other hotels.Keyword— Analysis Audit Energy; Electrical Energy; Energy Utilization; Hotel Sintesa Peninsula Manado Abstrak — Dengan meningkatnya kebutuhan energi listrik maka keandalan suatu sistem tenaga listrik juga harus berbanding lurus dengan kebutuhan energi listrik. Analisis Audit Energi adalah teknik yang dipakai untuk menghitung besarnya konsumsi energi pada bangunan gedung dan mengenali cara – cara untuk penghematannya. Analisis Audit Energi Hotel Sintesa Peninsula Manado, bertujuan untuk mengetahui penggunaan energi dan Kondisi pemanfaatan energi serta peluang penghematan energi di Hotel Sintesa Peninsula Manado. Dari data yang diperoleh dari beberapa ruangan, ada yang belum memenuhi kriteria dan ada juga ruangan yang sudah memenuhi kriteria dari audit energi. dari analisa ini digunakan perencanaan untuk mengoptimalkan penggunaan energi listrik serta pemanfaatan energi lain di Hotel Sintesa Peninsula Manado agar dapat lebih ekonomis dan dapat juga menjadi salah satu acuan untuk prehotelan yang lain.Kata Kunci— Audit Energi Listrik; Energi Listrik; Hotel Sintesa Peninsula Manado; Pemanfaatan Energi